ANALISIS BIAYA RELEVAN : MENERIMA ATAU MENOLAK PESANAN KHUSUS DI PT. AQUAMAS INDAH - Ainun Arizah (AkMen JURNAL ILMIAH, 2019)
This study aims to determine the relevant cost calculation of PT. Aquamas Indah and analyze relevant costs for making decisions to accept or reject special orders. The analytical method used starts with calculating production costs and then classifying existing cost data into relevant and irrelevant costs, then separating semi-variable costs into fixed costs and variable costs, then conducting relevant cost analysis. The results of the analysis of relevant costs indicate that special orders from PT. Multi Sari Fisindo and PT. Sumber Baru can benefit the company. So it was concluded that the special order was acceptable.